2011
DOI: 10.4049/jimmunol.1002709
|View full text |Cite
|
Sign up to set email alerts
|

CD23-Bound IgE Augments and Dominates Recall Responses through Human Naive B Cells

Abstract: Human peripheral blood BCRμ+ B cells express high levels of CD23 and circulate preloaded with IgE. The Ag specificity of CD23-bound IgE presumably differs from the BCR and likely reflects the Ag-specific mix of free serum IgE. CD23-bound IgE is thought to enhance B cell Ag presentation to T cells raising the question of how a B cell might respond when presented with a broad mix of Ags and CD23-bound IgE specificities. We recently reported that an increase in CD23+ B cells is associated with the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…We reported that CD23 cross-linking is an important mediator in B cell signaling, particularly of Syk activation (21). Besides the role that CD23-bound IgE plays, B cells have been shown to transport immune complexes to follicular dendritic cells (FDC) in the GC in a CD21-dependent manner (12).…”
Section: Cxcr5mentioning
confidence: 99%
See 4 more Smart Citations
“…We reported that CD23 cross-linking is an important mediator in B cell signaling, particularly of Syk activation (21). Besides the role that CD23-bound IgE plays, B cells have been shown to transport immune complexes to follicular dendritic cells (FDC) in the GC in a CD21-dependent manner (12).…”
Section: Cxcr5mentioning
confidence: 99%
“…We demonstrated that CD23-bound, parasite-specific IgE induces kinase activation in B cells, but the role(s) of these signaling pathways in host resistance remains unclear (21). Indeed, the immunobiology of CD23 is highly complex.…”
mentioning
confidence: 95%
See 3 more Smart Citations